Neutral Caputo-Fabrizio Fractional Differential Equation with Hyers-Ulam Stability - Rohman, Minanur; Eryilmaz, Ilker; Huda, M. N. (Universitas Brawijaya, 2023)
In this paper, we will discuss the existence and uniqueness of a neutral Caputo-Fabrizio differential equation which fulfills several required conditions. Furthermore, using the Picard operator, we show that the problem has Hyers-Ulam type stability.